Perceptions of barriers and facilitators to implement programs for prevention of mother-to-child transmission of HIV-Mozambique - Olimpia Buleza Lamucene; Margarita Bernales; Lisette Irarrázabal Vargas; Lilian Ferrer Lagunas (SciELO, 2022)
Abstract Objective: To understand the perspectives of pregnant and postpartum women living with HIV in Sofala, Mozambique, regarding barriers and facilitators to following Prevention of Mother-to-Child Transmission (PMTCT) recommendations. Method: Qualitative study conducted in three health centers and with a peer support group of women living with HIV, between October 2020 and March 2021. We applied purposeful sampling, semi-structured interviews, and content analysis. Results: Among the barriers that emerged were the social stigma associated with HIV-positive status and fear of discrimination, side effects of medications, economic barriers, and denial of diagnosis/treatment. As facilitating factors: peer support networks and inspiration, innate concern for health and family. Finally, they recommend that the community should become more educated about HIV. Conclusion: The results of this study give a broad understanding of the experience of women living with HIV in this province, making it possible to focus strategies in improving the care of women in PMTCT programs in Mozambique.